2018
DOI: 10.5155/eurjchem.9.2.147-150.1733
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of (2E)-1-(4-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one

Abstract: The compound, C16H14O3, (except H atoms) is almost planar [r.m.s. deviations for all non-H atoms = 0.001 Å] and the dihedral angle between the aromatic rings is 9.35 (7)°. In the crystal, molecules are linked by intermolecular O—H···O and C—H···O hydrogen bonds, forming a three-dimensional network structure. Furthermore, a weak π-π stacking interactions [centroid-to-centroid distance = 3.7055 (9) Å] contributes to the stabilization of the molecular packing. Crystal Data for C16H14O3 (M = 254.27 g/mol): Orthorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…To assign the absolute configuration of 5, its X-ray diffraction data was obtained using Cu Kα radiation. Its X-ray crystallographic data showed a space group of Pbca (Yesilyurt et al, 2018;Cai et al, 2019). Detailed X-ray crystallographic analysis showed that compound 5 was a racemate, and the indole ring and the oxazole ring were almost coplanar in 5 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…To assign the absolute configuration of 5, its X-ray diffraction data was obtained using Cu Kα radiation. Its X-ray crystallographic data showed a space group of Pbca (Yesilyurt et al, 2018;Cai et al, 2019). Detailed X-ray crystallographic analysis showed that compound 5 was a racemate, and the indole ring and the oxazole ring were almost coplanar in 5 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%